Preparation method of alumina carrier
By adding water-soluble and oil-soluble polymer extrusion aids to aluminum hydroxide filter cake, alumina supports can be directly formed, solving the problems of complex processes, high costs, and insufficient side pressure strength in existing technologies. This enables the preparation of high-strength alumina supports suitable for hydrogenation catalysts.
Patent Information
- Application Number
- CN202410547276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-11-07
AI Technical Summary
Existing alumina support preparation technology is complex, costly, and causes serious dust pollution. Furthermore, the acid solution during the molding process damages the pore structure, resulting in insufficient lateral pressure strength and affecting the performance of the hydrotreating catalyst.
An extrusion aid containing water-soluble and oil-soluble polymers is added to the aluminum hydroxide filter cake. The atomized spray molding process avoids the use of acid solutions and directly forms the alumina carrier, thereby improving the lateral pressure strength.
The preparation process was simplified, the cost was reduced, dust pollution and pore structure damage were avoided, and the lateral compressive strength of the alumina support reached more than 140 N/cm, which meets the requirements of the hydrogenation catalyst.
Smart Images

Figure BDA0004823044190000081
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of industrial catalysis, and relates to a preparation method of an alumina carrier. BACKGROUND
[0002] With the deepening of environmental protection concept, the quality standard of clean fuel is continuously improved, and the oil refinery continuously upgrades the hydrogenation production device to improve the product quality. The importance of hydrogenation catalyst is increasingly prominent. In order to better solve the market demand, the catalyst researchers not only need to improve the comprehensive performance of the catalyst, but also need to further optimize the production process of the catalyst to reduce the cost in the production process of the catalyst, so as to ensure that the catalyst has stronger competitiveness.
[0003] The alumina carrier is one of the hydrogenation catalyst carriers which are widely used at present. The existing preparation technology of the alumina carrier is generally as follows: firstly, an aluminum hydroxide filter cake is prepared, then the filter cake needs to be dried and crushed to prepare aluminum hydroxide powder, and then nitric acid solution is added for molding, and after drying and calcining, the alumina carrier is obtained. CN1088397C discloses a preparation method of alumina suitable for being used as a heavy oil hydrogenation catalyst carrier, which comprises the following steps: contacting an aluminum compound solution with a precipitator solution to obtain a slurry containing aluminum hydroxide, filtering and washing the slurry to obtain an aluminum hydroxide filter cake, and then drying, crushing and molding the filter cake to obtain the alumina carrier. The preparation technology involves the processes of drying, crushing and powder feeding of the aluminum hydroxide filter cake, and the process is complex, the production cost is high, dust pollution is caused, and the environmental friendliness is poor. Further, the addition of the acid solution, especially the nitric acid solution, in the molding process will damage the pore structure of the alumina, and the calcining process will also cause ammonia-nitrogen pollution. SUMMARY
[0004] The inventors found in the research process that, instead of drying and crushing the aluminum hydroxide filter cake to prepare aluminum hydroxide powder, the aluminum hydroxide filter cake is directly molded, and at the same time, no acid solution is added in the molding process, and the obtained alumina carrier has a low side pressure strength. However, as a main component of the hydrogenation treatment catalyst, the side pressure strength of the alumina carrier has an important influence on the performance of the hydrogenation treatment catalyst. In order to avoid the excessive crushing of the hydrogenation treatment catalyst in the loading, use and regeneration processes, ensure the normal operation of the device and improve the recovery rate of the catalyst, it is usually required that the side pressure strength of the alumina carrier is ≧140 N / cm.
[0005] Based on the above research results, the present application provides a preparation method of an alumina carrier. The method does not use acid solution, can directly mold the aluminum hydroxide filter cake, and obtains an alumina carrier with good side pressure strength, which meets the requirements of the hydrogenation treatment catalyst for the side pressure strength of the carrier.
[0006] According to the first aspect of the present application, a preparation method of an alumina carrier is provided, comprising the following steps: adding an extrusion aid to an aluminum hydroxide filter cake, kneading to plasticity, then performing shaping, and then performing drying and calcination to obtain the alumina carrier; the extrusion aid contains a water-soluble polymer and an oil-soluble polymer, the water-soluble polymer is selected from one or more of polyethylene glycol 600, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 8000, polypropylene glycol 200, polypropylene glycol 400 and polypropylene glycol 600, and the oil-soluble polymer is selected from one or more of polypropylene glycol 1000, polypropylene glycol 4000 and polypropylene glycol 8000.
[0007] In the above preparation method, the dry basis content of the aluminum hydroxide filter cake is 34-48 wt%, preferably 36-46 wt%.
[0008] In the above preparation method, the aluminum hydroxide filter cake can be purchased through commercial channels, or can be prepared by any one of the existing technologies, such as carbonization method, aluminum sulfate method, aluminum chloride method and alcohol aluminum hydrolysis method.
[0009] In the above preparation method, the addition amount of the extrusion aid accounts for 2.3-5.5 wt% of the mass of the aluminum hydroxide filter cake (dry basis), preferably 2.5-5.2 wt%.
[0010] In the above preparation method, the mass ratio of the water-soluble polymer to the oil-soluble polymer in the extrusion aid is 1.5:1-6.0:1, preferably 1.5:1-5.5:1.
[0011] In the above preparation method, the extrusion aid can be added to the aluminum hydroxide filter cake in the form of an emulsion, and preferably the extrusion aid is added to the aluminum hydroxide filter cake in the form of an emulsion by means of atomization spraying; the specific operation process is as follows: the water-soluble polymer and the oil-soluble polymer are added to water, and then stirred to form an emulsion; then the extrusion aid is added to the aluminum hydroxide filter cake by means of atomization spraying; wherein the amount of water accounts for 10-38 wt% of the mass of the aluminum hydroxide filter cake (dry basis), preferably 10-35 wt%.
[0012] In the above preparation method, an auxiliary agent can also be added, and there is no requirement for the addition sequence of the extrusion aid and the auxiliary agent, and preferably the extrusion aid and the auxiliary agent are simultaneously added to the aluminum hydroxide filter cake; the auxiliary agent is selected from one or more of a titanium-containing compound, a silicon-containing compound, a boron-containing compound, a phosphorus-containing compound, a zirconium-containing compound and a fluorine-containing compound, preferably selected from one or more of metatitanic acid, tetraethyl titanate, tetrabutyl titanate, acidic silica sol, boric acid, ammonium borate, phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, zirconium nitrate, zirconium oxychloride, zirconium tetrachloride and ammonium fluoride; the addition amount of the auxiliary agent (in terms of element) accounts for 0.3-4.0 wt% of the mass of the aluminum hydroxide filter cake (dry basis).
[0013] In the preparation method, the molding can adopt any one of the means capable of realizing molding of the carrier in the prior art, such as extrusion molding. The shape of the molding is not particularly limited, and various shapes can be made according to requirements, such as any one of a spherical shape, a tablet, a ring shape, a hollow cylinder and a strip shape, preferably a strip shape, and different sizes can also be made according to requirements.
[0014] In the preparation method, the drying temperature is 100-160°C, the drying time is 2-8h; the calcination temperature is 550-850°C, and the calcination time is 2-6h.
[0015] According to a second aspect of the present application, the alumina carrier obtained by the above method is provided.
[0016] In the alumina carrier, the lateral pressure strength of the alumina carrier is ≧140N / cm, preferably ≧150N / cm.
[0017] In the alumina carrier, the pore volume of the alumina carrier is 0.66-0.95cm 3 / g, the specific surface area is 190-340m 2 / g, and the bulk density is 39.0-58.0g / 100mL.
[0018] Compared with the prior art, the preparation method of the alumina carrier provided by the present application has the following advantages:
[0019] 1. In the preparation method of the alumina carrier, the extrusion aid is added to the aluminum hydroxide filter cake, and the extrusion aid contains water-soluble polymer and oil-soluble polymer, which contains abundant hydroxyl groups that can interact with the surface aluminum hydroxyl groups of the aluminum hydroxide filter cake, thereby increasing the polymerization force between the particles during molding, thereby improving the lateral pressure strength of the alumina carrier.
[0020] 2. In the preparation method of the alumina carrier, the aluminum hydroxide filter cake can be directly molded without using an acid solution, thereby obtaining the alumina carrier, avoiding the problems of pore structure damage and ammonia-nitrogen pollution caused by the use of the acid solution, and omitting the drying and crushing steps of the aluminum hydroxide filter cake, thereby effectively optimizing the process and saving costs. DETAILED DESCRIPTION
[0021] The technical solutions of the present application will be further described below through examples and comparative examples, and it should be understood that the specific embodiments described are only limited to illustrating and explaining the present application, and are not used to limit the present application.
[0022] In the method, the extrusion aid contains water-soluble polymer and oil-soluble polymer, wherein the water-soluble polymer can be dissolved in water; the oil-soluble polymer is insoluble in water and can be dissolved in an organic solvent, which is one or more of toluene, ethanol and the like.
[0023] In the method, the specific surface area and pore volume of the alumina carrier are determined by low-temperature nitrogen physical adsorption method on a Micromeritics TriStar II 3020 adsorption instrument, the sample is activated at 350℃ under vacuum for 3h, and the adsorption-desorption isotherm of the calcined alumina carrier is determined at liquid nitrogen temperature.
[0024] In the method, the side pressure strength of the alumina carrier is tested according to the provisions of Q / SHFRIPP 040023.
[0025] In the method, the test method of the dry basis content of the aluminum hydroxide filter cake is as follows: taking an appropriate amount of sample with a mass of m1, calcining at 500℃ for 3h, then measuring the mass as m2, calculating the mass percentage of the sample after calcination and the sample before calcination m2 / m1×100%, which is the dry basis content of the sample.
[0026] Example 1
[0027] The aluminum hydroxide filter cake is prepared by carbonization method, and the steps are as follows: preparing 2L sodium metaaluminate solution with a concentration of 21g / 100mL, adjusting the temperature to 25℃, gradually introducing carbon dioxide with a volume concentration of 40% into the solution, controlling the aeration time to be 5min, then adjusting the pH of the system to 8.6, and aging at 80℃ for 2h; then washing with deionized water for three times, and separating to obtain aluminum hydroxide filter cake with a dry basis content of 39wt%.
[0028] 7.6g of polyethylene glycol 2000 and 4.2g of polypropylene glycol 4000 are weighed and added to 41.4g of water, and a emulsion is formed by high-speed stirring at 2000r / min for 0.5h. During the kneading process, the emulsion is uniformly added to 1000g of aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and extruded into strips using a three-leaf clover hole plate with a diameter of 1.7mm. The formed carrier is dried at 120℃ for 5h and calcined at 600℃ for 5h to obtain the alumina carrier ZT-1.
[0029] Example 2
[0030] The aluminum hydroxide filter cake was prepared by aluminum sulfate and sodium metaaluminate neutralization method, and the steps were as follows: 4.2 g / 100 mL aluminum sulfate and 22 g / 100 mL sodium metaaluminate solution were synchronously added into the reaction container, the temperature of the reaction system was 80 ℃, and the neutralization pH value was 8.3. After the neutralization reaction was completed, the slurry was continuously aged for 2 h under the above conditions. Then, the slurry was filtered, and the filter cake was washed with deionized water for 3 times, and the aluminum hydroxide filter cake with a dry basis content of 45 wt% was obtained by separation.
[0031] 16.3 g of polyethylene glycol 600 and 6.7 g of polypropylene glycol 8000 were weighed into 101.2 g of water, and a milky liquid was formed by high-speed stirring at 2000 r / min for 0.5 h. During the kneading process, the milky liquid was uniformly added to 1000 g of aluminum hydroxide filter cake by atomizing spray. After the material was kneaded into a plastic body, it was transferred to an extruder, and was extruded into strips using a three-leaf clover hole plate with a diameter of 1.7 mm. The formed carrier was dried at 120 ℃ for 5 h and calcined at 600 ℃ for 3 h to obtain an alumina carrier ZT-2.
[0032] Example 3
[0033] The aluminum hydroxide filter cake was prepared by aluminum sulfate and sodium metaaluminate neutralization method, and the steps were as follows: 4.2 g / 100 mL aluminum sulfate and 22 g / 100 mL sodium metaaluminate solution were synchronously added into the reaction container, the temperature of the reaction system was 80 ℃, and the neutralization pH value was 8.3. After the neutralization reaction was completed, the slurry was continuously aged for 2 h under the above conditions. Then, the slurry was filtered, and the filter cake was washed with deionized water for 3 times, and the aluminum hydroxide filter cake with a dry basis content of 45 wt% was obtained by separation.
[0034] 16.3 g of polyethylene glycol 600 and 6.7 g of polypropylene glycol 8000 were weighed into 101.2 g of water, and a milky liquid was formed by high-speed stirring at 2000 r / min for 0.5 h. During the kneading process, the milky liquid was uniformly added to 1000 g of aluminum hydroxide filter cake by atomizing spray. After the material was kneaded into a plastic body, it was transferred to an extruder, and was extruded into strips using a three-leaf clover hole plate with a diameter of 1.7 mm. The formed carrier was dried at 120 ℃ for 5 h and calcined at 600 ℃ for 3 h to obtain an alumina carrier ZT-2.
[0035] Example 4
[0036] The aluminum hydroxide filter cake was prepared by aluminum sulfate and sodium metaaluminate neutralization method, and the steps were as follows: 4.2 g / 100 mL aluminum sulfate and 22 g / 100 mL sodium metaaluminate solution were synchronously added into the reaction container, the temperature of the reaction system was 80 ℃, and the neutralization pH value was 8.3. After the neutralization reaction was completed, the slurry was continuously aged for 2 h under the above conditions. Then, the slurry was filtered, and the filter cake was washed with deionized water for 3 times, and the aluminum hydroxide filter cake with a dry basis content of 45 wt% was obtained by separation.
[0037] Take 13.5 g of polyethylene glycol 4000 and 3.9 g of polypropylene glycol 4000 into 70.6 g of water, and form an emulsion by high-speed stirring at 2000 r / min for 0.5 h. During the kneading process, the emulsion is uniformly added to 1000 g of aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and extruded into a strip using a three-leaf clover hole plate with a diameter of 1.7 mm. The formed carrier is dried at 120°C for 5 h and calcined at 820°C for 3 h to obtain an alumina carrier ZT-4.
[0038] Example 5
[0039] Take 1000 g of aluminum hydroxide filter cake with a dry basis content of 42 wt% purchased from Shanxi Ju Hua New Material Technology Co., Ltd.
[0040] Take 14.3 g of polyethylene glycol 8000 and 3.4 g of polypropylene glycol 1000 into 152.3 g of water, and form an emulsion by high-speed stirring at 2000 r / min for 0.5 h. During the kneading process, the emulsion is uniformly added to the aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and extruded into a strip using a three-leaf clover hole plate with a diameter of 1.7 mm. The formed carrier is dried at 120°C for 5 h and calcined at 750°C for 3 h to obtain an alumina carrier ZT-5.
[0041] Example 6
[0042] Take 1000 g of aluminum hydroxide filter cake with a dry basis content of 44 wt% purchased from Shanxi Ju Hua New Material Technology Co., Ltd.
[0043] Take 10.1 g of polyethylene glycol 6000 and 6.8 g of polypropylene glycol 4000 into 52.3 g of water, and form an emulsion by high-speed stirring at 2000 r / min for 0.5 h. During the kneading process, the emulsion is uniformly added to the aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and extruded into a strip using a three-leaf clover hole plate with a diameter of 1.7 mm. The formed carrier is dried at 120°C for 5 h and calcined at 750°C for 3 h to obtain an alumina carrier ZT-6.
[0044] Example 7
[0045] Take 1000 g of aluminum hydroxide filter cake with a dry basis content of 37 wt% purchased from Shanxi Ju Hua New Material Technology Co., Ltd.
[0046] Take 14.4 g of polyethylene glycol 6000 and 2.3 g of polypropylene glycol 8000 and mix into 81.4 g of water, high-speed stirring for 0.5 h to form an emulsion. In the kneading process, the emulsion is evenly added to the aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and a three-leaf clover hole plate with a diameter of 1.7 mm is used to extrude and form a strip. The formed carrier is dried at 120°C for 5 h and calcined at 820°C for 3 h to obtain an alumina carrier ZT-7.
[0047] Comparative Example 1
[0048] The preparation process of the aluminum hydroxide filter cake is the same as that of Example 3.
[0049] In the kneading process, 68.4 g of water is evenly added to 1000 g of filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and a three-leaf clover hole plate with a diameter of 1.7 mm is used to extrude and form a strip. The formed carrier is dried at 120°C for 6 h and calcined at 600°C for 3 h to obtain an alumina carrier DZT-1.
[0050] Comparative Example 2
[0051] The preparation process of the aluminum hydroxide filter cake is the same as that of Example 3.
[0052] Take 12.3 g of polyethylene glycol 8000 and mix into 68.4 g of water, high-speed stirring for 0.5 h to form an emulsion. In the kneading process, the solution is evenly added to 1000 g of aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and a three-leaf clover hole plate with a diameter of 1.7 mm is used to extrude and form a strip. The formed carrier is dried at 120°C for 5 h and calcined at 600°C for 3 h to obtain an alumina carrier DZT-2.
[0053] Comparative Example 3
[0054] The preparation process of the aluminum hydroxide filter cake is the same as that of Example 3.
[0055] Take 12.3 g of polypropylene glycol 1000 and mix into 68.4 g of water, high-speed stirring for 0.5 h to form an emulsion. In the kneading process, the emulsion is evenly added to 1000 g of aluminum hydroxide filter cake by atomizing spray. After the material is kneaded into a plastic body, it is transferred to an extruder, and a three-leaf clover hole plate with a diameter of 1.7 mm is used to extrude and form a strip. The formed carrier is dried at 120°C for 5 h and calcined at 600°C for 3 h to obtain an alumina carrier DZT-3.
[0056] Comparative Example 4
[0057] The preparation process of the aluminum hydroxide filter cake is the same as that of Example 3.
[0058] Take 5 g of cellulose and 4 g of sesbania powder, and mix with aluminum hydroxide filter cake in a kneader, and add 68.4 g of water evenly during kneading. After the material is kneaded into a plastic body, transfer to an extruder, and use a 1.7 mm diameter three-leaf clover hole plate to extrude into strips. Dry the formed carrier at 120°C for 5 h, and calcine at 600°C for 3 h to obtain an aluminum oxide carrier DZT-4. The properties of the aluminum oxide carriers prepared in the above examples and comparative examples are shown in Table 1.
[0059] Table 1 Properties of aluminum oxide carriers obtained in examples and comparative examples
[0060]
[0061]
[0062] As can be seen from Table 1, the side pressure strength of the carrier obtained by the preparation method of the present application is significantly improved, and can all reach above 150 N / cm.
Claims
1. A process for the preparation of an alumina support, characterized in that: The method comprises the following steps: The extrusion aid is added to the aluminum hydroxide filter cake, and kneaded into a plastic body, and then formed, and then dried and calcined to obtain the aluminum oxide carrier; The extrusion aid contains water-soluble polymer and oil-soluble polymer, the water-soluble polymer is selected from one or more of polyethylene glycol 600, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 8000, polypropylene glycol 200, polypropylene glycol 400 and polypropylene glycol 600, and the oil-soluble polymer is selected from one or more of polypropylene glycol 1000, polypropylene glycol 4000 and polypropylene glycol 8000.
2. The method of claim 1, wherein: The dry basis content of the aluminum hydroxide filter cake is 34-48 wt%, preferably 36-46 wt%.
3. The method of claim 1, wherein: The amount of the extrusion aid added is 2.3-5.5 wt% of the mass of the aluminum hydroxide filter cake (dry basis), preferably 2.5-5.2 wt%.
4. The method of claim 1, wherein: The mass ratio of the water-soluble polymer to the oil-soluble polymer in the extrusion aid is 1.5:1-6.0:1, preferably 1.5:1-5.5:
1.
5. The method of claim 1, wherein: The extrusion aid is added to the aluminum hydroxide filter cake in the form of an emulsion, and preferably the extrusion aid is added to the aluminum hydroxide filter cake in the form of an emulsion by means of atomization spraying; the specific operation process is as follows: the water-soluble polymer and the oil-soluble polymer are added to water, and then stirred to form an emulsion; then the extrusion aid is added to the aluminum hydroxide filter cake by means of atomization spraying; wherein the amount of water is 10-38 wt% of the mass of the aluminum hydroxide filter cake (dry basis), preferably 10-35 wt%.
6. The method of claim 1, wherein: An additive is also added, and preferably the extrusion aid and the additive are simultaneously added to the aluminum hydroxide filter cake; the additive is selected from one or more of titanium-containing compounds, silicon-containing compounds, boron-containing compounds, phosphorus-containing compounds, zirconium-containing compounds and fluorine-containing compounds, and preferably is selected from one or more of metatitanic acid, tetraethyl titanate, tetrabutyl titanate, acidic silica sol, boric acid, ammonium borate, phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, zirconium nitrate, zirconium oxychloride, zirconium tetrachloride and ammonium fluoride; the amount of the additive added (in terms of elemental substance) is 0.3-4.0 wt% of the mass of the aluminum hydroxide filter cake (dry basis).
7. The method of claim 1, wherein: The forming is performed by extrusion forming; the shape of the formed product is any one of spherical, tablet, ring, hollow cylinder and strip, and preferably is strip.
8. The method of claim 1, wherein: The drying temperature is 100-160°C, and the drying time is 2-8h; the calcination temperature is 550-850°C, and the calcination time is 2-6h.
9. The aluminum oxide carrier prepared by the method of any one of claims 1-8.
10. The alumina support of claim 9, wherein: The side pressure strength of the aluminum oxide carrier is ≧140 N / cm, preferably ≧150 N / cm.
11. The alumina support of claim 9, wherein: The alumina support has a pore volume of 0.66 to 0.95 cm 3 / g, a specific surface area of 190 to 340 m 2 / g, and a bulk density of 39.0 to 58.0 g / 100 mL.
Citation Information
Patent Citations
Preparation of alumina suitable for being used as catalyst carrier for hydrgenating heavy oil
CN1088397C